Facile impedimetric analysis of neuronal exosome markers in Parkinson’s disease diagnostics - Tofaris, GK; Fu, Y; Jiang, C; Davis, J (American Chemical Society, 2020)
The egress of α-synuclein in neuronally derived exosomes predates the clinical presentation of Parkinson’s disease (PD), offering a means of developing a predictive or prognostic test. Here, we report the reagentless impedimetric assay of two internal exosome markers (α-synuclein and syntenin-1) from neuronal exosomes. Exosomes were efficiently extracted from patient sera using anti-L1CAM conjugated zwitterionic polymer-modified magnetic beads prior to lysis and analyzed by electrochemical impedance spectroscopy. The quantification of α-synuclein level across 40 clinical samples resolved statistically significant differences between PD patients and healthy controls (HC).